Strategi Pengembangan Destinasi Wisata Mangrove Oleh Pemerintah Desa Babakan Pangandaran - Serly Nisa Ulzanah; Agus Nurulsyam Suparman; Adityawarman Adityawarman (Jurnal Kajian dan Penelitian Umum, 2024)
This research is motivated by the Babakan Village, Pangandaran District, Pangandaran Regency which is not yet optimal in terms of the Mangrove Tourism Development Strategy by the Government. The aim of this research is to determine the Mangrove Tourism Development Strategy by the Babakan Village Government, Pangandaran District, Pangandaran Regency. The method used in this research is a descriptive qualitative research method. Data collection techniques include: Interview observation and documentation. The data processing techniques in this research are: data collection, data reduction, data presentation and drawing conclusions. The locus of this research is Babakan Village, Pangandaran District, Pangandaran Regency. Based on the initial survey conducted by the author, it can be seen that the Mangrove Tourism Development Strategy by the Babakan Village Government, Pangandaran District, Pangandaran Regency has not been running optimally. The indicators of problems that arise include: 1. The village government is not improving development planning with community leaders in collaborating on mangrove tourism. 2. The village government does not introduce mangrove tourism enough so that there are still many people outside who do not know or recognize the existence of the Pangandaran tourist village. 3. The village government does not provide adequate support in terms of facilities and infrastructure.